A Review of Strategies for Managing Uncertainty in Crude Oil Prices by Indonesian Oil and Gas Companies and the Government - Syamsul Ma'arif; Dyah Ari Susanti; Dian Tiara Rezalti; Aisyah Indah Irmaya; Lia Yunita; Dila Damayanti; Yunita Fitri Wahyuningtyas (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2022)
The world oil and gas market has experienced uncertainty since 2014 until now. Fluctuating supply and demand, geopolitical tensions, and shifts in energy policies cause this. In addition, at the beginning of 2020, there was a prolonged pandemic, which made oil and gas conditions even more erratic. This uncertainty significantly impacts the Indonesian state, especially the Indonesian government and oil and gas companies operating in Indonesia. Various methods have been taken to mitigate the impact of this uncertainty, both by the government and oil and gas companies. Therefore, this study aims to conduct a literature review regarding the strategies undertaken by the Indonesian government and oil and gas companies in Indonesia to address the uncertainty in world oil prices since 2018. This research was conducted using the literature method. A review of scientific articles that have been published from 2018 to 2022. The selected articles follow the research objectives and comply with the inclusion and exclusion criteria set at the outset. Results of the literature process the review obtained as many as 67 articles that discussed various strategies carried out by the government and oil and gas companies. The discussion results show three strategies carried out by oil and gas companies in Indonesia: cutting costs, implementing digitalization, and diversifying into renewable energy projects. Meanwhile, the strategy undertaken by the Indonesian government includes providing fiscal incentives, investing in infrastructure that supports the oil and gas sector, deregulating the oil and gas sector, and encouraging the use of renewable energy as an alternative energy source. These various strategies aim to increase efficiency, reduce costs, diversify energy sources, and increase competitiveness in Indonesia's oil and gas sector to deal with the uncertainty of world oil prices.